The radiological and histological investigation of the dental follicle of asymptomatic impacted mandibular third molars - Kuncai Li; Wei Xu; Tiejun Zhou; Junliang Chen; Yun He (BMC, 2022)
Abstract Objectives The indication for removal of asymptomatic fully impacted third molars is still controversial. In this study, radiological and histological investigation of the dental follicle of asymptomatic impacted mandibular third molars was performed, aiming to provide a reference for clinical prophylactic extraction of these teeth. Methods Patients with impacted mandibular third molars were included and the maximum width of the dental follicle around the crown was measured in horizontal, sagittal and coronal sections by cone beam computed tomography. The dental follicles were stained with haematoxylin-eosin, analysed by a pathologist and classified as normal, inflammatory or cystic. A Chi-squared test was used to analyse the association of the incidence of inflammation and cysts with the clinical variables of the impacted mandibular third molars. Results Thirty-seven samples were normal dental follicles; 52 samples showed inflammatory infiltration with an incidence of 57.14%; 2 samples with a maximum dental follicle width of 2-3 mm were diagnosed as odontogenic cysts, and the incidence was 2.20%. There was no significant difference in the incidence of inflammatory and cystic dental follicles between males and females, or between different age groups (P > 0.05). With an increase of the maximum width of the dental follicle, there was a rise in the incidence and degree of infiltration of chronic nonspecific inflammation. Conclusion Asymptomatic impacted mandibular third molars tend to be extracted, especially for teeth with a 2-3 mm maximum width of the dental follicle on radiological examination.